Metode Storytelling pada Pembelajaran Tahfidz Al-Qur’an Anak Usia Madrasah Ibtidaiyah - Rajaie Al Makhzum, Wazien; Suharsono (IBTIDA’, 2025)
Effective learning methods play a crucial role in enhancing children’s interest and ability to memorize the Qur’an. This study aims to explore the use of the storytelling method in Qur’an memorization (tahfidz) learning for Madrasah Ibtidaiyah-aged children. Storytelling was chosen because it creates a joyful learning atmosphere while stimulating children’s imagination and memory. This research adopts a descriptive qualitative approach with observation, interviews, and documentation as data collection techniques. The findings show that the storytelling method successfully increases children’s active engagement in the tahfidz learning process. By incorporating stories containing Qur’anic values and narratives of the prophets, children find it easier to understand and memorize Qur’anic verses. Additionally, this method is effective in instilling noble character traits in children. In conclusion, storytelling is a relevant and innovative strategy to boost motivation and Qur’an memorization achievements among Madrasah Ibtidaiyah-aged children